Matura??o de frutos e viabilidade de sementes de Physalis ixocarpa Brot. ex Hormen - Barroso, Nat?lia dos Santos (2015)
The Physalis genus occupies a prominent position in the Solanaceae family for fruit production for consumption in natura, by presence of poly-oxygenated metabolites and vitasteroids in their tissues, especially physalins, which are attributed some pharmacological activities. Due to large amount of seeds produced by fruits and the fact these seeds germinate easily in different environments, the species of this genus become easy grow. Predicting the ideal point of harvest can lead to increased exploration capabilities of this feature also contributes to obtaining more vigorous seeds for use in studies of propagation and conservation of this important genus. This paper aims to monitor the maturation of fruits and seed viability during fruit development stages. During flowering, the flowers in anthesis were tagged daily until obtaining the number of enough fruit for evaluation. P. ixocarpa fruit were collected at 15, 25, 35, 45, 55 days after anthesis (DAA). In a sample of 50 fruits, it is measuring the length, diameter, fresh weight, color, soluble solids, number and weight of seeds per fruit. The color and pigment content calyx were evaluated and correlated. To determine the quality of seeds at different times of maturation, newly harvested seeds and after drying at room were evaluated for water content, dry mass, germination and seedling emergence. The fruits of P. ixocarpa have more pronounced changes in color only in the calyx. Changes occur in the physical and chemical characteristics to 35 DAA, not differing significantly from the following stages. The physiological seed quality was highest at 45 DAA, indicating this is the best time of maturity for harvest seeds, when the calyx is completely or partially broken and has the yellow green and light yellow brown color and dark green fruit.